Fucoidan as a renal protectant: mechanistic insights and therapeutic implications of endothelial glycocalyx targeting - Xin, Ping; Ge, Chengqiao; Tang, Yufan; He, Yifan; Fu, Bin (Frontiers in Pharmacology, 2026)
The progression of chronic kidney disease (CKD) is closely associated with damage to the endothelial glycocalyx (eGC) of the renal microvasculature. The eGC, particularly its heparan sulfate (HS) components, is crucial for maintaining the charge-selective barrier and microenvironmental homeostasis. Modern pharmacological investigations of marine brown algae (e.g., Saccharina japonica), traditionally used in medicine for conditions such as “edema,” reveal that their principal active component, fucoidan, is a sulfated polysaccharide with marked physicochemical similarities to endogenous HS. This review systematically posits that the core mechanism underlying the nephroprotective effects of fucoidan, as a natural product, lies in its direct targeting and repair of the damaged eGC. Through a systematic literature search up to November 2025, this review elucidates that fucoidan, especially its low-molecular-weight fractions, can consolidate and reconstitute the glycocalyx structure via dynamic integration, competitive substitution, and activation of intracellular signaling pathways. This central action not only directly restores the renal charge barrier and reduces proteinuria but also, by stabilizing endothelial function, systemically inhibits the inflammation and fibrosis cascades triggered by glycocalyx injury. The efficacy of fucoidan in diverse preclinical models, coupled with clinical trial evidence for fucoidan-based drugs in human CKD patients, collectively supports the validity of a glycocalyx-targeted therapeutic strategy. We conclude that fucoidan represents a natural product derived from traditional wisdom, with a defined molecular mechanism and translational potential, offering a promising complementary strategy for the comprehensive management of CKD.